Processes of enhanced self‐understanding during a counselling programme for parents of children with disabilities. Issue 1 (24th May 2012) - Haugstvedt, Karen Therese Sulheim; Graff‐Iversen, Sidsel; Bukholm, Ida Rashida Khan; Haugli, Liv; Hallberg, Ulrika
Abstract : Scand J Caring Sci; 2013; 27; 108–116 Processes of enhanced self‐understanding during a counselling programme for parents of children with disabilities Background:  The stress and burden on parents of children with disabilities are well documented, and the parents' way of handling the situation is crucial to the health and well‐being of all family members, including the child with special needs. We conducted a group‐based counselling programme for parents, based mainly on Gestalt education and personal construct theories, aiming at increasing the parents' ability to handle the situation. Aims:  To explore the parents' experiences from processes of change after the counselling programme. Method design:  This qualitative study is based on modified grounded theory. Method:  The study conducted in Norway examines the experiences of 67 parents (of whom 29 fathers) of children with disabilities. Information was collected through focus group discussions after finishing their sessions of the counselling programme. Findings:  From the parents' experiences, the following categories were developed: feeling motivated to communicate, describing oneself in new words, being inspired to experience one's own emotions, being more present and in charge and making a difference by taking new steps. The core category in our analysis turned out to be Improved handling of the situation by enhanced self‐understanding. The parents seemed to redevelop their self‐understanding through new experiences of themselves. They emphasized the importance of a secure setting of peers with similar experiences and skilled counsellors to feel free to explore one's own emotions with connecting thoughts and bodily reactions. Discussion of existential issues as one's own values also contributed to enhanced self‐understanding, which strengthened the parents to find new possibilities and priorities in handling the situation. Conclusions:  The parents described subjective processes of awareness and self‐reflection as important for being able to start a process towards enhanced self‐understanding, which helped to detect one's own values and new ways of acting. These experiences may be relevant for the parents and for the conduction of future counselling.